1989
DOI: 10.1128/mcb.9.6.2453
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of amino acids in pp60c-src that are phosphorylated by protein kinases C and A.

Abstract: in pp6Ocsrc and in pp60c.src(F5271 (a mutant whose transforming activities are enhanced by Tyr-527-*Phe mutation) by transfecting single-, double-, and triple-mutant src expression plasmids into NIH 3T3 cells. Tryptic phosphopeptide analyses of the mutant proteins confirmed prior biochemical identifications of the phosphorylation sites and showed that neither separate nor coordinate mutations at Ser-12 and Ser-17 affected Tyr-416, Tyr-527, or Ser-48 phosphorylation or prevented mitosis-specific phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…Hirota et al reported that overexpressed c-src mutated at this residue exhibits a slight elevation in kinase activity in chicken embryo fibroblasts with no morphological alteration (23). Similarly, mutation of pp60c-sr and pp6Oc-src(F527) at Ser-17 does not affect the specific activity or transforming activity of these proteins in NIH 3T3 cells (57). We found that overexpression of c-src mutated at Ser-17 in 10T1/2 fibroblasts was not associated with a striking alteration in either specific kinase activity of the protein or agonist-induced cAMP accumulation, indicating that phosphorylation on this residue may not contribute to potentiation of 13-agonist signalling mediated by c-src kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Hirota et al reported that overexpressed c-src mutated at this residue exhibits a slight elevation in kinase activity in chicken embryo fibroblasts with no morphological alteration (23). Similarly, mutation of pp60c-sr and pp6Oc-src(F527) at Ser-17 does not affect the specific activity or transforming activity of these proteins in NIH 3T3 cells (57). We found that overexpression of c-src mutated at Ser-17 in 10T1/2 fibroblasts was not associated with a striking alteration in either specific kinase activity of the protein or agonist-induced cAMP accumulation, indicating that phosphorylation on this residue may not contribute to potentiation of 13-agonist signalling mediated by c-src kinase.…”
Section: Discussionmentioning
confidence: 99%
“…4A): spot 1 (protein kinase A-phosphorylated phosphoserine 17 [27]), spots 3 and 4 (PTyr-527 [7]), spots 5 and 6 (protein kinase C-phosphorylated phosphoserine 12 [14,43)], and spot 7 (protein kinase C-phosphorylated phosphoserine 48 [14,43]). c-Src(LN), c-Src(R295), and c-Src(R295/LN) from unsynchronized cells displayed similar maps except that spots 5, 6, and 7 (Ser-12 and Ser-48) were not observed in the nonmyristylated mutants ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively there is evidence that c-Src is phosphorylated by PKA at serine 17 (38,39), and this phosphorylation is known to decrease the hydrophobicity of c-Src and enhance the release of c-Src from the cytoplasmic membrane to the cytosol (21,40,41). PKA may therefore increase translocation of c-Src from the cell membrane to the cytosol, thus decreasing its ability to phosphorylate a relevant substrate and modulate NMDA channels.…”
Section: Role Of C-src In the Pdgf-induced Depression-intracellularmentioning
confidence: 99%